INTERNALISASI NILAI-NILAI PENDIDIKAN KARAKTER DALAM AJARAN TAREKAT QADIRIYAH WA NAQSYABANDIYAH DI PONDOK PESANTREN AN-NAWAWI BERJAN PURWOREJO - Ngatoillah Linnaja (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2018)
This study included the type of qualitative research at the An-Nawawi Islamic BoardingSchool in Berjan Purworejo in 2016, by taking primary data through direct interviewswith the managers and administrators of the educational institutions. secondary data,obtained through literature that has relevance to research. The instrument used in this studywas observation, and interviews. The analysis uses deductive, inductive, and descriptivemethods. The results of the study showed: (1) Congregation is a way of referring to asystem of meditation and charity, which is a guide in performing worship in accordancewith the teachings exemplified by the Prophet to the teachers who connect continuouslywithout interruption. Qodiriyah Wa Naqsabandiyah congregation is a combination of twocongregations, namely Qodiriyah and Naqsabandiyah so that it becomes a new tarekat,founded by an Indonesian Sufi named Sheikh Ahmad Khotib Sambas. The teachings ofthis tarekat generally have five main points: First, studying science which deals with theimplementation of all orders, second; accompanying teachers and friends as closely aspossible to see how to do a service, third; abandon all rukhah and ta'wīl to guard andmaintain charity perfection, fourth; keep and use time and fill it with all wirid and prayerin order to strengthen the khusyu'an and hūdur, and fifth; curb yourself not to get out oflust and keep yourself awake; (2) Qodiriyah Wa Naqsyabandiyah Congregation at the An-Nawawi Islamic Boarding School in Berjan Purworejo, the subject matter of its teachingshas not changed, and the genealogy of its leadership is carried out in stages from KH.Achmad Chalwani, from his father KH. Nawawi, from his father, Shaykh Zarkasyi, whostudied with Sheikh Abd al-Karim, a student of the founder of the Sheikh Ahmad KhotibSambas congregation; (3) The Teachings of the Qodiriyah Wa Naqsyabandiyah Orderat an-Nawawi Islamic Boarding School Berjan Purworejo, have a major contribution inshaping the values of the character of the santri, namely: religious, honest, disciplined,hard work, humble, respect for knowledge, and respect and courtesy.